النصّ القرآنيّ في فكر توشیهیكو إیزوتسو دراسة وصفیة تحلیلیة تطبیقیة لحقول كلمة (ریب) الدلالیة - نويدي, عبدالوحيد; طالب پور, دانا (University of Eloued جامعة الوادي, 2024)
الخطوة الأولی في عملیة الترجمة هي الكشف عن معاني الألفاظ وعلی المترجم أن یسیر في هذه الخطوة على ضوء نظريات عالم دلالي للحصول علی المعاني. ومن هذا المنطلق، قام إیزوتسو بدراسة معاني الألفاظ القرآنیة في الشعر الجاهلي وبادر إلی تعریف الألفاظ السیاقي والاستبدالي والألفاظ المتضادة والحقل الدلالي للألفاظ وصورتها المنفیة والألفاظ المترادفة وتوظیفها في السیاق غیر الدیني. یقوم البحث الحالي بدراسة كلمة (الریب) الدلالیة معتمدا علی المراحل الأربعة الأولی متخذا منهجا وصفیا تحلیلیا. قد اقترنت كلمة (الریب) في الشعر الجاهلي بألفاظ ك(المنون) و(الأحداث) و(الزمن) و(الدهر) وتدلّ علی المعاني التالیة: الأحداث المُرّة والموت وإلخ، وقد استعملت في القرآن الكريم عبارة (ریب المنون) مرة واحدة في المواضيع الدینیة. قد شوهد لـ(لریب) استعمالات یكون معناه الصحیح شك وعداوة ونقمة. ومن أجل النقل الكامل للحقول الدلالیة إلی لغة المقصد، قد اقترحت التسلسل العنادي الوصفي. The first step in the translation process is to reveal the meanings of words, and the translator must follow this step in the light of the theories of the semantic world to obtain the meanings. From this standpoint, Izutsu studied the meanings of Qur’anic words in pre-Islamic poetry and took the initiative to define contextual and substitutive words, antonyms, the semantic field of words, their negative forms, and synonymous words, and employ them in the non-religious context. The current research studies the semantic word “doubt” based on the first four stages, adopting a descriptive and analytical approach. In pre-Islamic poetry, the word (doubt) was associated with words such as (the event), (events), (time), and (time), and denoted the following meanings: bitter events, death, etc., and the phrase (doubt of the event) was used in the Holy Qur’an once in topics. Religious. It has been seen that uses of (lareeb) are in its correct meaning: doubt, enmity, and resentment. In order to fully transfer the semantic fields to the target language, I proposed the descriptive metasequence.
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي
Keywords: القرآن الكریم، علم الدلالة، إیزوتسو، الریب، الشك العنادي; Quran; Semantics; Izutsu; doubt; Stubborn Doubt.